Interpretations an ethnographic drama - Blackledge, Adrian 1959-; Creese, Angela 1959- (Multilingual Matters, 2021)
"This highly original book brings compelling narratives of migration and social diversity vividly to life. At once a play script and an outcome of ethnographic research, this book is a rich resource for the interpretation and representation of life in the multilingual city. This text is an ethnographic drama based on audio-recordings, field notes, and interviews collected at Chinese Community Centre, Birmingham, as part of a research project which examined communication in multilingual, superdiverse cities. Characters are fictionalised versions of community centre workers, clients, and researchers who agreed to participate in the research."--
Keywords: Migration; Ethnolinguistik; Ethnomethodologie; Chinese / England / Birmingham / Drama; Immigrants / England / Birmingham / Drama; Multilingualism / England / Birmingham / Drama; Theaterstück